Anxiety and depression related to the hospitalization experience of patients receiving radioiodine ablation - Koc, Z.; Karakoc, A.; Balci, T.; Kepenek, F.; Atmaca, M. (Springer, 2013)
[Abstract Not Available]
Annual Congress of the European-Association-of-Nuclear-Medicine (EANM) -- OCT 19-23, 2013 -- Lyon, FRANCE
Keywords: ablation; depression; anxiety; thyroid carcinoma